Greetings from the barricades : revolutionary postcards in Imperial Russia - Mathew, Tobie (2018)
Amid the chaos and violence of the 1905 Revolution in Russia, the Tsar's opponents printed and distributed vast quantities of picture postcards. Easy to share, hide and smuggle, postcards were a way to beat the censor and spread a message of defiance. Produced by a diverse set of revolutionaries, liberals, and opportunists, the content of these cards is equally wide-ranging: from satirical caricatures directed against the government to rare photographs of revolutionary demonstrations. Many of the cards are darkly humorous, combining laughter with a sense of raw indignation at the injustices of Imperial Russia